A ANALISIS KETIDAKTERTIBAN PARKIR KENDARAAN RODA DUA MAHASISWA UPI DALAM PERSFEKTIF PANCASILA - Bagas Yudhistira (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2025)
Disorderly parking behavior among motorcycle-riding students at Universitas Pendidikan Indonesia (UPI) remains a persistent issue that disrupts campus order and affects other road users. This study explores the reasons behind students’ tendency to park improperly, including laziness to walk upstairs, limited lift availability, the urge to reach class quickly, and inadequate parking facilities and security. The research aims to analyze these behaviors from the perspective of students themselves in order to formulate more effective and student-centered parking management strategies. Using a descriptive qualitative approach, data were collected through field observations and student surveys. The findings indicate that many students consciously choose convenience over rules due to poorly designed parking structures and minimal supervision. As a result, this study recommends improving the parking environment by adding higher-capacity lifts, increasing surveillance on upper parking levels, and enhancing overall parking comfort and order. These improvements are expected to foster a more responsible parking culture among students.